FeCl3‐Catalyzed Diastereodivergent Sulfamidation of Diarylmethanol Diastereomixtures Bearing a Chiral Auxiliary Dependent on Catalyst Loading. Issue 12 (17th November 2021) - Oda, Ryoga; Yamamoto, Hiroshi; Nakata, Kenya
Abstract: The FeCl3 ‐catalyzed, diastereodivergent sulfamidation of diastereomixtures of diarylmethanols bearing a chiral auxiliary was achieved and was found to be dependent on the catalyst loading. Under these conditions, a variety of substrates bearing different substituents on their aromatic rings could be applied to both reaction pathways. The sulfamide moieties were easily removed to give the corresponding chiral amines. Chiral sulfamides with different stereochemistry were efficiently synthesized as organocatalysts using the present method. Abstract : Diastereodivergent sulfamidation of diastereomixture of diarylmethanols bearing a chiral auxiliary was achieved with high selectivity depend on the Lewis acid catalyst loading under the mild reaction conditions.